Q-switched Raman fiber laser with titanium dioxide based saturable absorber - Hisamuddin, N.; Jusoh, Z.; Zakaria, U. N.; Zulkifli, Mohd Zamani; Latiff, A. A.; ,, M. Yasin; Ahmad, H.; Harun, S. W. (National Institute of Optoelectronics, 2017)
We demonstrate a Q-switched Raman fiber laser (RFL) using a newly developed Titanium dioxide (TiO2) film based saturable absorber (SA). The SA is fabricated by mixing the dispersed TiO2 suspension into a polyvinyl alcohol solution to form a precursor which is then transformed into a thin film through a drying process at room temperature. It is sandwiched between two fibre ferrules and inserted in a Raman fiber laser cavity with a total cavity length of about 8 km. Self-started pulse train operating at 1558.5 nm is generated as the pump power is increased from 398 mW to 431 mW with a repetition rate that can be tuned from 131.4 to 142.5 kHz. The smallest pulse width of 2.97 μs and the highest energy of 5.81 nJ are obtained at pump power of 431 mW and 427 mW, respectively. These results show that the TiO2 embedded in polymer film has a great potential to be used for pulse generation in Raman fiber laser system.